A divided nation: which antibiotic first for meningococcal disease in children and infants? a national survey. (29th September 2015) - Hudson, L; Tickner, N; Salt, P
Abstract : Background: Meningococcal bacteria isolated from cases of invasive disease in the UK remain fully sensitive to both ceftriaxone and cefotaxime. However, concerns over safety when using ceftriaxone in conjunction with calcium-containing drugs has led to cautions from regulatory bodies and guidelines. Aims: To survey all paediatric units in England and Wales to ascertain their current guidelines for antibiotic prescribing for treatment of suspected meningococcal disease. Methods: Anonymous postal survey of all hospitals with resident acute paediatric services in England and Wales on first line antibiotic use for suspected meningococcal disease in children and infants. Our local ethics committee deemed this audit not requiring further research committee approval. Results: 223 hospitals were identified as having acute paediatric units, from which 170 (76%) responses were received. First-line antibiotic is closely split between ceftriaxone (82 units; 48%) and cefotaxime (76 units; 45%). 96 (52%) units using ceftriaxone as first line (exclusively or as either cefotaxime or ceftriaxone) have no exceptions for using it in guidelines. Few units using ceftriaxone caution specifically about concomitant calcium use (14%) or its use in younger infants (12%). Although the vast majority of units perceived that their guidelines were adhered with 84 (49%) saying always and 81 (48%) saying mostly, only 61 (36%) had conducted an audit. Conclusions: Antibiotic choice is divided across England and Wales. Consequences of using calcium and ceftriaxone concomitantly are likely to be rare, but severe. Forthcoming National Institute for Health and Clinical Excellence guidelines may create consistency.